Utilization of Extensively Available Environmental Waste Mentha spicata for Uptake of Pb(II) from Aqueous Solutions - Riaz, Beenish; Mahmood Ansari, Tariq; Asif Hanif, Muhammad; Riaz, Sana; Aslam Khan, Muhammad; Riaz, Muhammad; Idrees Jilani, Muhammad (Asian Journal of Chemistry, 2013)
The present study was focused on extensively available Mentha spicata distillation waste biomass for Pb(II) uptake from aqueous solutions. The biomass was entrapped in alginate bead after adopting a specially carried out process. The effect of various experimental parameters on adsorption of Pb(II) was investigated under laboratory conditions. The results clearly indicated the importance of various experimental parameters such as pH, biosorbent dose, biosorbent particle size, initial metal concentration and contact time for removal of Pb(II) from aqueous solutions. The uptake of Pb(II) by immobilized Mentha spicata distillation waste biomass increased with increase in pH reaching a maximum at 5. The equilibrium sorption data agrees well with Freundlich sorption isotherm with high correlation coefficients. The kinetics of the sorption process was found to follow pseudo-second order kinetic model in batch mode and pseudo-first order in continuous mode of adsorption. High Pb(II) uptake capacity of immobilized Mentha spicata distillation waste biomass suggested that it could be used as a potential biomaterial to remove Pb(II) ions from aqueous solutions.